Synthesis and Characterization of Novel Triazine Schiff ’s Bases Complexes with Transition Metal(II) Ions (International Journal of Scientific Research in Science and Technology, 2025)
1,3,5-triazines are a very important class of six- membered aromatic heterocyclic compounds receiving much attention in scientific research. This study focuses mainly on synthesis of 1,3,5- triazine derivative (TRIPOD) and TRIPOD-Schiff’s Bases by using microwave irradiation and their metal complexes with transition metal (II) ions. Schiff’s Bases synthesized from TRIPOD with different substituted aniline and metal (II) complexes of copper (II), nickel(II) and cobalt(II) of Tripod-Schiff’s bases were obtained in good yield. The characterization of newly synthesized compounds has been carried out by using FTIR, UV, XRD. The absorption peaks of Schiff’s bases synthesized and their complexes shows absorption peaks at different frequencies. TRIPOD shows characterized peak at 1567 cm-1 due to- CHO whereas all compounds have a conjugate system of double bonds on their backbone. The x-ray diffraction Spectrum of TRIPOD shows characteristic of crystalline and amorphous phases of conventional semi-crystalline compounds. Spectrum of complexes indicates amorphous nature of TRIPOD-SBNA complexes. FTIR spectra of TRIPOD gives characterized peak at 1567 cm-1 due to -CHO. Whereas Tripod-Schiff’s bases and their complexes gives peak which are in good arrangement with Literature values.